Automated methods to accelerate fungal red listing: a case study for North American macrofungi - Vida J. Svahnström; Steven Bachman; Cátia Canteiro; Eimear Nic Lughadha; A. Martyn Ainsworth; Jessica L. Allen; Scott T. Bates; Matilda J.M. Brown; Susana P. Cunha; Anders Dahlberg; Susana C. Gonçalves; Tom W. May; et al. (Fungal Ecology, 2026)

Recognition of the discipline of conservation mycology - Tom W. May; Jerry A. Cooper; Anders Dahlberg; Giuliana Furci; David W. Minter; Gregory M. Mueller; Alison Pouliot; Zhuliang Yang (Conservation Biology, 2019)
Article impact statement : Conservation mycology is a newly introduced discipline relevant to conservation biologists, mycologists, ecologists, and conservation policy.

A new species of Ceratocladium from Spain - Julio Mena-Portales; Margarita Hernández-Restrepo; David W. Minter; Josepa Gené (Mycological Progress, 2011)

Global diversity and distribution of macrofungi - Gregory M. Mueller; John P. Schmit; Patrick R. Leacock; Bart Buyck; Joaquín Cifuentes; Dennis E. Desjardin; Roy E. Halling; Kurt Hjortstam; Teresa Iturriaga; Karl-Henrik Larsson; D. Jean Lodge; Tom W. May; et al. (Biodiversity and Conservation, 2007)